Body, Nature, Language : Artisans to Artists in the Commodification of Authenticity - Heller, Monica; Pietikäinen, Sari; da Silva, Emanuel (University of Toronto Press, 2017)
This article examines processes of authenticating and selling handicrafts at the conjuncture of cultural pride and economic profit in two peripheral sites (Finnish Sámiland and rural Québec), under shared conditions of late capitalism and globalising political economies. These conditions (re)structure traditionalist and modernist discourses about artisans' historical bodies, their connections to the local land (nature), and how they interactionally authenticate and sell their products through language. Under these conditions, the commodification of authenticity pushes artisans and handicrafts beyond being emblems of national belonging and collective tradition, and toward individualised, artistic commercial production with greater or lesser ties to post-national cosmopolitanism. Cet article examine les processus d'authentification et de vente l'artisanat à la croisée de la fierté culturelle et du profit économique dans deux sites périphériques (en Laponie finlandaise et au Québec rural), sous les conditions communes du capitalisme tardif et des politiques économiques mondialisées. Ces conditions (re)structurent les discours traditionalistes et modernisants sur les corps historisés des artisans, leurs liens avec la terre locale (la nature), et modifient la manière dont ils authentifient et vendent leurs produits de façon interactionnelle à travers la langue. Dans ces conditions, la commodification de l'authenticité pousse les artisans et l'artisanat au-delà d'emblèmes d'appartenance nationale et de tradition collective, vers la production artistique individualisée et commerciale, avec des liens plus ou moins importants au du cosmopolitisme post-national. peerReviewed